A novel high efficient Mg–Ce–La adsorbent for fluoride removal: kinetics, thermodynamics and reusability. Issue 50 (26th October 2016) - Wu, Liying; Zhang, Gaoke; Tang, Dandan
Abstract: A novel Mg–Ce–La adsorbent was prepared by a facile co-precipitation method and was used for fluoride removal. The as-obtained adsorbent has a large specific surface area of 118.6 m 2 /g and exhibited high fluoride removal efficiency of 97.5%, which may be attributed to the ion-exchange between the hydroxyl ion and fluoride ion. The fluoride adsorption over the Mg–Ce–La adsorbent could reach its equilibrium in about 40 min and follow the Freundlich model and the pseudo-second-order model. In addition, the Mg–Ce–La adsorbent showed high adsorption performance over a wide pH range from 3.0 to 8.0 for fluoride removal, which would be beneficial for practical application. Finally, the Mg–Ce–La adsorbent still exhibited high fluoride removal rate after four reused cycles.